Anticipation and its degrees of critical-reflective radicality: opening up the affordances of engaging with futures to problematize STI - Sergio Urueña (Journal of Responsible Innovation)
Anticipation is increasingly recognized as a valuable dimension for promoting more responsible STI practices. Various normative frameworks acknowledge anticipation as a means to enable critique and/or reflection. However, the degrees of critique and reflection that anticipation can or should enable have remained under-researched. By exploring the critical-reflective affordances that anticipation could offer for problematizing STIs in the present, this article aims to advance the theoretical development of anticipation as a dimension for promoting more responsible STIs. The article suggests that the potential critical-reflective radicality of anticipation is modulated by the critical-reflective spaces of problematization and/or scrutiny afforded by the normative frameworks in which anticipation is interpreted and for which it is enacted. Against this background, the article provides some tentative variables for assessing these critical-reflective affordances and specifies the roles that different modes of anticipation might play in opening up distinct, interconnected aspects of STI to problematization and/or scrutiny.